2007
DOI: 10.1007/s11257-007-9037-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of learner’s affect from conversational cues

Abstract: We explored the reliability of detecting a learner's affect from conversational features extracted from interactions with AutoTutor, an intelligent tutoring system (ITS) that helps students learn by holding a conversation in natural language. Training data were collected in a learning session with AutoTutor, after which the affective states of the learner were rated by the learner, a peer, and two trained judges. Inter-rater reliability scores indicated that the classifications of the trained judges were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
153
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(162 citation statements)
references
References 71 publications
0
153
0
9
Order By: Relevance
“…In this case, it is difficult for instructors to identify the struggling, confused and even frustrated students. Previous research has indicated that positive emotion helps to promote students' learning interests and engagement levels (Altrabsheh, Cocea, & Fallahkhair, 2015;D'Mello et al, 2008), and students with an upsurge of emotion may have higher motivation to accomplish their learning goals. Ramesh, Goldwasser, Huang, Daumé III, & Getoor (2013) incorporated the positive/negative score of post content into engagement metrics to distinguish between disengaged and engaged learners in MOOC forums.…”
Section: Emotional States Of Students In Course Forumsmentioning
confidence: 99%
“…In this case, it is difficult for instructors to identify the struggling, confused and even frustrated students. Previous research has indicated that positive emotion helps to promote students' learning interests and engagement levels (Altrabsheh, Cocea, & Fallahkhair, 2015;D'Mello et al, 2008), and students with an upsurge of emotion may have higher motivation to accomplish their learning goals. Ramesh, Goldwasser, Huang, Daumé III, & Getoor (2013) incorporated the positive/negative score of post content into engagement metrics to distinguish between disengaged and engaged learners in MOOC forums.…”
Section: Emotional States Of Students In Course Forumsmentioning
confidence: 99%
“…We try to capture potentially overlapping emotions, adding an additional level of complexity to the modeling task. Second, [12] targets longerterm states that some researchers may classify as moods, i.e., states that are less specific than simple emotions, less likely to be triggered by a particular stimulus, and lasting [10]. We see these longer-term affective states as being complementary to the more instantaneous emotions we focus on, as we discuss in a later section.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, most work on affect recognition has focused on detecting one specific emotion (e.g., [4][5][6]), lower-level affective measures of valence and arousal (e.g., [7,9]) or overall emotional predisposition over a complete interaction (e.g., [10,11]). One exception is the work by D'Mello et al, [12], which used dialogue features as predictors of student's boredom, confusion, flow and frustration during interaction with a dialogue-based tutoring system. There are three main differences between this work and ours.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations